PERAN TOKOH AGAMA DALAM PEMBERANTASAN NARKOBA - Mustajab, Muhammad; Handayani, Putri (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2022)
This study aims to determine the efforts of religious leaders of Pidie Regency in eradicating drugs, as well as to find out the obstacles faced by religious leaders of Pidie Regency in eradicating drugs. This research method uses descriptive analysis method, the method of data collection is library research and field research. Researchers conducted research using question instruments in the form of observations, interviews, and review of documentation. The results of this study are the efforts of religious leaders in eradicating drugs in Pidie Regency, namely religious leaders must work together and together to eradicate drugs, convey the dangers of drugs to the community through da'wah, pulpit sermons, lectures, discussions both with the government and with the community at In both informal and official meetings, religious leaders together with imum syik in the village area also play a role in formulating the gampong pageu (gampong qanun), the aim of which is to maintain order and environmental security. The obstacles faced by religious leaders in Pidie Regency in eradicating drugs are, religious leaders have limited information and facilities, lack of attention from community support, regional leaders or community leaders in all regions.